ANALYSIS OF PUBLIC OPINION ON E-GOVERNMENT MANAGEMENT AND TOURISM POLICY IN EAST JAVA - Ali Fathoni; Rohmatul Fitriyah Dewi; Muhammad Chusnul Khitam; Akhmad Imam Amrozi; Iva Milatul Chanifah (Jurnal Ekonomi, 2022)
Indonesia is rich for its natural resource potential and cultural diversity, in particular, East Java Province is well-known for its tourism. As an effort to develop tourism, the E-Government management of East Java Province establishes the policies regarding tourism development. In the development of tourism, the East Java Provincial Government cannot be separated from the principles of sustainable development. This study aims to describe and analyze the role of the East Java Provincial Government in implementing tourism development policies based on community responses and various stakeholders in the tourism environment. This study uses a qualitative descriptive research method. Sources of data used are primary data (questionnaires) via online, and secondary data (interviews and documentation). The results of this study found that the implementation of tourism development policies in East Java Province received the responses from the society and various stakeholders with good E-Government Management principles, through improving: (1) service quality, (2) transportation quality, ( 3) quality road access, (4) security, (5) information transparency, (6) innovation strategy, (7) rule of law and (8) policy quality. In addition, the East Java Provincial Government must play an active role in implementing these policies as a general policy maker and licensing regulation, as well as policies that favor the society and control private parties investing in East Java Province.